From Croatia to Cape Town : the future of the World Archaeological Congress - Kitchen, Willy
'Ruffled feathers' seem to be part of the world Archaeological Congerss. Here we present two different assessments of the forthcoming World Archaelogical Congress in Cape Town in JanuaryÐone from an observer, Willy Kitchen, and one frm the WAC Secretary, Julian Thomas, which set out some of the ideals and current realities of this highly political enterprise.